Synthesis and analysis of an integrated suspension energy harvesting system for continuous half-width speed bumps - Min-Chie Chiu; Ho-Chih Cheng; Ming-Guo Her; Mansour Karkoub (Journal of Low Frequency Noise, Vibration and Active Control)
Global warming and climate change have become an important issue that the world is focusing on due to its apparent impact on lives and economies around the world. Efforts have been put into developing more environmentally friendly vehicles ranging from hybrid to fully electrical vehicles. In addition, research efforts have been made to develop and embed energy harvesters in vehicles to reuse some of the energy usually released into the environment. This study is about the development of an energy harvesting suspension system and investigates its performance using a continuous half-width deceleration bump. A 3D vehicle model with 4 harvesters embedded in the suspension is used in the analysis. The focus is on the effect of harvesters’ parameters and speed bump’s physical characteristics on the power generation performance of the harvesters. The main objective is to maximize electricity and minimize the ride comfort efficiency index using a multi-objective optimization function in conjunction with a genetic algorithm. This study proposes an innovative self-powering method that utilizes a chassis energy harvester to convert vibrations into magnetoelectric effects. It enables autonomous green energy generation for transportation vehicles and can be applied to vehicles traversing consecutive speed bumps. In addition to effectively reducing speed, the energy harvester generates green electricity to supplement the power supply of electric vehicles.